Comprehending Qualifying Payment Amount (QPA) and the No Surprise Act in Healthcare - Koranchirath, Nithin Narayan (International Journal of Health Sciences, 2024)
Purpose: This article investigates the No Surprise Act, a pivotal piece of legislation designed to protect consumers from unexpected out-of-network healthcare charges, emphasizing the Qualifying Payment Amount (QPA) mechanism. Methodology: Through a comprehensive literature review, analysis of legislative texts, and examination of case studies, this study elucidates the Act's origins, objectives, and operational framework of the QPA. It also explores the challenges of implementing the Act, its impact on various stakeholders (patients, healthcare providers, and insurers), and the broader implications for the U.S. healthcare system. Despite its intentions to curb surprise billing practices, the No Surprise Act and its QPA component face several implementation challenges, including administrative burdens, disputes over payment calculations, and unintended consequences on insurance premiums and healthcare market dynamics. This article leverages recent data, expert opinions, and comparative analysis with other healthcare models to provide a nuanced evaluation of the Act's effectiveness and areas for improvement. Findings: The findings suggest that while the No Surprise Act represents a significant step forward in patient financial protection, ongoing adjustments and policy refinements are essential for achieving its intended outcomes without compromising the sustainability of healthcare providers and insurers. Unique Contributor to Theory, Policy and Practice: Study and policy recommendations aims to contribute to the ongoing dialogue and efforts to enhance patient protection and healthcare affordability in the U.S., ensuring that the No Surprise Act lives up to its promise and potential..